Doxazosin oral intake therapy to relieve stent - related urinary symptoms and pain: a prospective, randomized, controlled study - Zhang,Long (2016)
ABSTRACT Objective: To assess the impact of Doxazosin Oral Intake Therapy on urinary symptoms and pain in patients with indwelling ureteral stents Patients and Methods: A total of 239 patients with ureteral stone-related hydronephrosis who underwent a double-J stent insertion after ureteroscopic lithotripsy were enrolled. Patients were randomized to receive doxazosin cotrolled release 4 mg once daily for 4 weeks or matching placebo. Patients completed the brief-form Chinese version Ureteric Stent Symptom Questionnaire (USSQ) and quality of life (QoL) score 2 weeks and 4 weeks after stent placement and 4 weeks after stent withdrawal. The analgesic use was also recorded during the stenting period. Results: Patients in Doxazosin Oral Intake Therapy group, in the first 2 weeks and second 2 weeks with the stent in situ, expressed significant lower daytime frequency (p=0.028 and p=0.038), nocturia (p=0.021 and p=0.008) and urgency (p=0.012 and p=0.014), respectively. Similarly, flank pain score, QoL score and analgesic use were also significant less in the stenting period. There was no significant difference in scores of urinary symptoms, pain and QoL during the post-stent period between two cohorts. Conclusions: Doxazosin Oral Intake Therapy reduced stent-related urinary symptoms, pain and the negative impact on QoL.